Formation of La-based perovskite compounds in supercritical water. Issue 11 (1st August 2018) - Abe, Yoshiyuki; Satou, Iwao; Aida, Tsutomu; Adschiri, Tadafumi
Abstract: Formation of La-based perovskite compounds, LaBO3 (B: Fe, Al, Mn, Co and Ni), in supercritical water was examined using a batch-type reactor vessel. Investigations of processing conditions revealed that the heat treatment of the equimolar nitrate solution of La and Fe with pH 8 at 450 °C and 30 MPa for 15 min was optimal for obtaining LaFeO3 as a single phase. Analysis of the products prepared under the conditions of the lower reaction temperature or the shorter reaction time elucidated the formation mechanism of LaFeO3 ; it was formed from a reaction of intermediate products of LaOOH and Fe2 O3 at 450 °C, and LaOOH was formed via La2 (OH)5.1 (NO3 )0.9 at the lower temperature. Adjustment of the pH of the nitrate solution to 8 by the addition of the KOH solution was important for the effective formation of the LaOOH intermediate and for the decrease in the formation of La2 (OH)5.1 (NO3 )0.9 or La(OH)3, which had a poor reactivity with Fe2 O3 or other iron-related compound at 450 °C and 30 MPa and remained as the secondary phase in the final product. The optimum conditions were applied to the synthesis of LaAlO3, LaMnO3, LaCoO3 and LaNiO3, and it was observed that a single phase of LaAlO3 was formed, while LaMnO3 was formed with several secondary phases, and LaCoO3 and LaNiO3 could not be formed at all. The ease of the formation of the La-based perovskites was mostly related to the sum of first, second and third ionization energies of B-site cations, which may mean that it is easy to form a B ion with a + 3 valence (Fe 3+, Al 3+, Mn 3+, Co 3+ and Ni 3+ ) in supercritical water.